Sosialisasi Elemen DNA Kota untuk Membangun Kemampuan Bersaing: Kolaborasi bersama Komunitas Peneliti Sosial Sains Universitas PUP, Philiphina - Djudjun Rusmiatmoko; Eko Nursanty; M. Fahd Diyar Husni; Susmita Eka Mukti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
City DNA is the elements that make up the uniqueness of a city. It is formed over a long period of time and passed down from one generation to the next. Heritage or heritage that forms the uniqueness of this city is in the form of physical / objects and intangible that strengthen each other. The purpose of socializing the DNA of the City is an understanding of the uniqueness of a place that is ultimately able to provide uniqueness to a place that is a destination for tourists. For international researchers, the introduction of City DNA is a way to be able to recognize the competitive ability of a place. Using the method of field visits and discussions with local communities, it is expected to get a direct picture of the authenticity of the city which is bottom up and used as a basic perception of foreign tourists and researchers in the city of Semarang.